New species and records of heterostigmatic mites (Acari: Prostigmata: Heterostigmata) phoretic on scarabaeid dung beetles (Coleoptera: Scarabaeidae) from northwestern Iran - Sobhi, Mohammad; Hajiqanbar, Hamidreza; Mortazavi, Azim (Zootaxa, 2017)
Four species of heterostigmatic mites (Acari: Heterostigmata: Dolichocybidae, Neopygmephoridae, Pygmephoridae) associated with scarabaeid dung beetles (Coleoptera: Scarabaeidae) are recorded from northwestern Iran. One of these is a new species, Pavania khiavensis Sobhi & Hajiqanbar sp. nov. (Dolichocybidae), described from under the metanotum of Euoniticellus fulvus. Other collected mites are as follows: Pavania gymnopleuri Hajiqanbar & Khaustov, 2010 (Dolichocybidae), Troxodania decumanus (Krczal, 1959) (Neopygmephoridae) and Pseudopygmephorellus szekessyi (Mahunka, 1970) (Pygmephoridae). The genus Troxodania is recorded for the first time from western Asia. New host beetle records are documented and a key to world species of the genus Pavania associated with scarabaeid beetles is also presented.